Comprehensive review on COVID-19: etiology, pathogenicity, and treatment - El Zawily, Amr; Eckert, Sarah; Adajar, Reed; Wagih, Nardin; Elmaidomy, Abeer H.; Helmy, Abdelrahman M.; Mustafa, Mazen; Elshorbagi, Mazhar; Ghali, Erin; Fadl, Rehab G.; Bodem, Jochen; Abdelmohsen, Usama Ramadan; et al. (Frontiers in Medicine, 2025)
With the unprecedented surge of severe COVID-19 cases in early 2020, researchers and medical professionals worked actively to identify effective viral infection treatments based on a scientific understanding of viruses. Over the past few years, an enormous amount of research has investigated the viral infection and replication processes following the first SARS-CoV-2 case. With this knowledge, many drugs have been explicitly created to inhibit viral replication or decrease the severity of the immune response. Additionally, scientists have utilized decades of research and techniques to expedite SARS-CoV-2 vaccine development. SARS-CoV-2, a positive-strand RNA virus, belongs to the Sarbecovirus subgroup of Betacoronaviruses. Its emergence is not unique; previous outbreaks like SARS and MERS have shaped our understanding of coronavirus-related diseases. Molecular clock analysis suggests that the ancestor of all current coronaviruses existed over 10,000 years ago, with subsequent evolution occurring around 3300–2400 BC. Researchers have explored synthetic and natural treatments alongside other antiviral therapies, corticosteroids, and immunotherapies. Additionally, using artificial intelligence and nano-based technologies enriched SARS-CoV-2 diagnosis and management. In this comprehensive review, we provide recent literature on COVID-19, exploring its evolving etiology, pathogenicity, and pathophysiology, alongside developments in synthetic and natural therapeutic strategies, vaccines, artificial intelligence in diagnosis, and nano-based technologies.